Gender Myth-Making in a Digital Beauty Campaign: Masculine Symbolism in the Somethinc x Batman Instagram Reels - Prita Eufho Anggraini; Ricardo Indra (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to analyze how feminine representations and the strength of Batman’s character are combined in Something’s beauty campaign, which was published via Instagram Reels videos. The approach used is a semiotic analysis based on Roland Barthes’ theory, which focuses on the meaning of signs and symbols in visual and verbal messages. This study examines how the soft, feminine image and Batman’s strong character complement each other to form a unique advertising message that captures the attention of a female audience. Data collection techniques include a literature review and observation of digital documents in the form of Somethinc x Batman campaign Reels videos taken from Somethinc’s official Instagram account. The data obtained was then analyzed using denotative significance, connotative significance, mythic revelation, and triangulation through the Expression, Relation, and Content (E-R-C) sign structure in Something’s Instagram Reels video content. The research findings indicate that the Something and Batman campaigns successfully created a more progressive and bold representation of femininity compared to conventional beauty advertisements. However, this representation remains a product of the commodification of heroism. The myth of strength constructed through the Batman character serves as a powerful emotional draw to attract modern female audiences, who yearn for agency and self-authority, yet are ultimately still directed to become consumer subjects within the 2025 digital beauty industry. Therefore, this study contributes to the understanding of the use of semiotics in digital marketing strategies that incorporate popular cultural symbols to influence consumer perceptions.